Integrated Paradigm of Lean Supply Chain of SMEs by Utilizing Customer Relationship Management Capabilities and Family Distribution Networks - Hayati Nufus; Wawan Ichwanudin (International Journal of Supply Chain Management, 2020)
This study aims to provide an explanation of the differences in the results of research regarding the relationship between the capabilities of management of customer relationships with marketing performance, through family distribution networks as a part of supply chain management with the object on food and beverage SMEs Banten Province, Indonesia. The testing of this empirical research model uses Structural Equation Modeling (SEM) using several software, namely AMOS 18.0, SPSS 20 and Excel 2013. The unit of analysis in this study was carried out with a census for SME managers with 191 sample sizes. The results reveal that customer relationship management capabilities and value creation in business are significantly related to family distribution networks. In addition, business network accessibility also plays a positive role in improving family distribution networks, and in marketing performance. Family distribution networks, as an originality offered in this study, significantly influence marketing performance. The results of this study underscore the importance of using family distribution networks to improve the effectiveness of supply chain management, physical product distribution and to improve SME marketing performance.